Utilization of Power Point Media Asean Materials in Improving Learning Results of Class VI Students Elementary School - Lailatul Badriatul Mubarokah; Yantoro Y; Habibah Anna Radmika; basyir b (Universitas Pendidikan Indonesia (UPI), 2024)
The aim of this research is to examine student learning outcomes. This research uses the Classroom Action Research (PTK) method. The subjects and location of this research were students in class VIC at SDN 42 Jambi City, totaling 31 students. The research model used is research research which includes four stages of action, namely planning, action, observation and reflection. The data analysis technique used is descriptive qualitative. The results of the research showed that students experienced significant improvement during the two cycles with each completion percentage. In the pre-cycle it reached 38.70% completeness, in cycle 1 it reached 64.5% completeness, and in cycle II it achieved 87.09% completeness or an increase of 48.39. With an average in the pre-cycle of 67.87 to 72.12 in cycle 1, and experiencing an increase in cycle II to 78.25.